Improving mathematical ability and student learning outcomes through realistic mathematic education (RME) approach - Lady, Agustina; Utomo, Bendot Tri; Chikita, Lovi (International Journal of Engineering and Technology, 2018)
This study was conducted based on preliminary study conducted by researchers who found that students' mathematical ability is still low to solve contextual problems, this will certainly have an impact on student learning outcomes that are less than the maximum. The purpose of this research is (1) To know the application of learning using Realistic Mathematics Education (RME) learning approach, (2) To know the improvement of students' mathematical ability on the story after using Realistic Mathematics Education (RME) learning approach, (3) improving student learning outcomes after using Realistic Mathematics Education (RME) learning approach. RME is a learning approach that emphasizes experiences, events, or something close to the real situation imaginable by students as a means of providing insight into math problems. The ability of mathematization is the ability of students to identify real-world problems and then translate them into sentences (mathematical models) and solve the model to get the solution of the real problem. Classroom Action Research (CAR) is conducted in SMP Negeri 2 Lumajang class VIII A 2016/2017 subject matter opportunities. This study consists of 2 cycles. In this research, it is found that (1) Realistic Mathematics Education (RME) implementation consists of understanding contextual problem, solving problems, comparing and discussing answers, and concluding. Percentage of achievement in the first cycle 72% increased in cycle II to 92%, (2) students' mathematization ability increased from cycle I to 77% then in cycle II reached 79%, (3) Percentage of learning achievement classic in cycle I reach 62,5% increase in cycle II to 81,25%. The average learning outcome of cycle I was 78.71 increasing in cycle II to 83.21. The conclusion can be obtained is the application of learning Realistic Mathematics Education (RME) able to improve the ability of mathematization and student learning outcomes in class VIII A SMP Negeri 2 Lumajang. Therefore, teachers are expected to improve students' mathematical skills in order to maximize learning outcomes by applying Realistic Mathematics Education (RME) learning.Â Â